Kebijakan Pemerintah Daerah Terhadap Status Dan Kedudukan Satuan Polisi Pamong Praja (Studi Di Kabupaten Kampar Provinsi Riau) - Retno Ade Widya Ningsih; Surya Perdana; Cakra Arbas (Iuris Studia: Jurnal Kajian Hukum, 2023)
The Civil Service Police is a functional position for Civil Servants, but in reality there are still Civil Service Police as casual daily workers. As in Kampar Regency, Riau Province. The research problems are the National Policy towards the Civil Service Police Unit, the Regional Government Policy towards the Position of the Civil Service Police Unit, and the obstacles and solutions implemented by the Regional Government. Normative legal research research that is descriptive analysis. The results of the research are that the National Policy towards the Civil Service Police Unit is not yet running optimally because the Civil Service Police Unit, which has non-PNS status, is assigned to assist ASN, which conflicts with its position as auxiliary workers. The Regional Government's policy regarding the position of the Civil Service Police Unit is not working well because the regional government still uses auxiliary personnel. The obstacles and solutions implemented by the Regional Government are limited funds, there is no legal umbrella for appointing Honorary Staff to become CPNS. The solution is to take action to change the status of THL to auxiliary staff, provide a salary system based on personnel diplomas, and provide health insurance and labor insurance